Hypoxia-Induced Mitogenic Factor Acts as a Nonclassical Ligand of Calcium-Sensing Receptor, Therapeutically Exploitable for Intermittent Hypoxia-Induced Pulmonary Hypertension. Issue 5 (May 2017) - Zeng, Xianqin; Zhu, Liping; Xiao, Rui; Liu, Bingxun; Sun, Mengxiang; Liu, Fangbo; Hao, Qiang; Lu, Yankai; Zhang, Jiwei; Li, Jiansha; Wang, Tao; Wei, Xiang; et al.
Abstract : Hypoxia-induced mitogenic factor (HIMF) is an inflammatory cytokine playing important role(s) in the development of hypoxic pulmonary hypertension. The molecular target mediating HIMF-stimulated downstream events remains unclear. The coimmunoprecipitation screen identified extracellular calcium-sensing receptor (CaSR) as the binding partner for HIMF in pulmonary artery smooth muscle cells. The yeast 2-hybrid assay then revealed the binding of HIMF to the intracellular, not the extracellular, domain of extracellular CaSR. The binding of HIMF enhanced the activity of extracellular CaSR and mediated hypoxia-evoked proliferation of pulmonary artery smooth cells and the development of pulmonary vascular remodeling and pulmonary hypertension, all of which was specifically attenuated by a synthesized membrane-permeable peptide flanking the core amino acids of the intracellular binding domain of extracellular CaSR. Thus, HIMF induces pulmonary hypertension as a nonclassical ligand of extracellular CaSR, and the binding motif of extracellular CaSR can be therapeutically exploitable. Abstract : Supplemental Digital Content is available in the text.